2017
DOI: 10.1007/s11695-017-3037-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Self-Regulation Moderates the Association Between Symptoms of ADHD and Weight Loss After Bariatric Surgery

Abstract: ESR moderated the association between sADHD and %EWL, suggesting that sADHD may attenuate weight loss following bariatric surgery among individuals deficient in ESR. This finding has implications for bariatric surgery pre-surgical psychological assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…which in turns favoured a better adherence to the weight loss programme. The conclusion of the Levy et al study are in line with the findings from another more recent clinical study [43] highlighting how symptoms of ADHD were associated with an attenuation of weight loss following bariatric surgery in 30 adults with severe obesity, accounted for by deficit in emotional regulation. Interestingly, the Levy et al study also resonates with the findings of a recent meta-analysis [44], showing that, compared to patients without ADHD, those with ADHD presented with a statistically significant reduction in postoperative follow-up (poor adherence to follow-up visits).…”
Section: Which Are the Implications Of The Link Adhd–obesity For Tsupporting
confidence: 82%
“…which in turns favoured a better adherence to the weight loss programme. The conclusion of the Levy et al study are in line with the findings from another more recent clinical study [43] highlighting how symptoms of ADHD were associated with an attenuation of weight loss following bariatric surgery in 30 adults with severe obesity, accounted for by deficit in emotional regulation. Interestingly, the Levy et al study also resonates with the findings of a recent meta-analysis [44], showing that, compared to patients without ADHD, those with ADHD presented with a statistically significant reduction in postoperative follow-up (poor adherence to follow-up visits).…”
Section: Which Are the Implications Of The Link Adhd–obesity For Tsupporting
confidence: 82%
“…Some studies show that ADHD symptoms are associated with high emotion dysregulation [117,135], impacting the ability to cope with daily difficulties, and involving greater negative affectivity and a higher risk of mood disorder comorbidity. As expected, some studies indicated that negative affectivity and emotion dysregulation mediates the association between ADHD and addictive-like eating behavior [108,109,112,126,135,[137][138][139], supported by publications which showed association between ADHD and emotional eating [126][127][128]. Negative affectivity and lack of emotion regulation, commonly observed in ADHD, would trigger food intake.…”
Section: Discussionsupporting
confidence: 55%
“…Williamson and colleagues (2017) [139] investigated the role of emotion self-regulation and ADHD symptoms in the weight loss of obesity patients after bariatric surgery. The interaction between ADHD symptomatology and emotion self-regulation accounted for 13% of the weight loss variance.…”
Section: Adultsmentioning
confidence: 99%
“…Few studies have examined the relationship between intelligence and weight loss outcome. A previous study reported that patients with poorly controlled developmental disorders showed insufficient weight loss after bariatric surgery [16], and the prevalence of mental retardation/developmental disorders tended to be higher in patients with %TWL <15% in the J-SMART study [6]. Few studies have reported weight loss outcomes in patients with binge eating.…”
Section: Discussionmentioning
confidence: 99%